PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, LEVERAGE DAN SALES GROWTH TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Masrullah Masrullah; Mursalim Mursalim; M. Su'un (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This study aims to analyze the influence of ownership of institutions, independent commissioners, leverage and sales growth on tax avoidance at Manufacturing companies in the Indonesia Stock Exchange.The type of data used in this study is quantitative data in the form of data in the form of numbers in the form of financial statements on manufacturing companies listed on the Indonesia Stock Exchange in the period 2014 to 2016. While the data analysis method used is multiple linear regression. The population in this study is 154 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research sample consisted of 18 companies, the period of 2014 to 2016. The sample technique used was purposive sampling.The results of this study indicate that institusional ownership and independent commissioner variables have no significant effect on tax avoidance. While leverage and sales growth variables have a significant effect on tax avoidance carried out on consumer goods sector companies in the period 2014 to 2016.